Hero in Augmented Reality (HEAR): Interactive Learning Media to Increase Learning Interest in Knowing about Indonesian Heroes for Kindergarten Student - Septyara Khotimaharani; Nissa Nur Azizah; Salma Rahmadianti; Angga Kahaerul; Hilda Yanuar Abadi; Fajar Nugraha Asyahidda (SEA-CECCEP, 2024)
Historical subjects are mandatory for kindergarten students. One of the best examples is to recognize every national hero of Indonesia to nurture high devotion to patriotism. But there are some problems such as the laziness to read some textbooks and the difficulties to memorize some long materials that sometimes come up to the student. With the use of the development of technology, this study aims to introduce several heroes in Indonesia through learning media which is a learning application based on augmented reality. This application can help kindergarten school learners to increase their insight or knowledge, especially on historical subjects. This research is using R&D (Research and Development). The main focus of this study is to design a digital learning application about national heroes in Indonesia. There are some features offered on this app including 3D (three dimensions) animations, audio features (audio information), and text is written materials based on augmented reality. 25 kindergarten school students responded and answered the questionnaire. The use of HEAR as a learning media can be increasing kindergarten students’ reading intention and knowledge, especially on how they recognize the Indonesian hero figure. This innovation is designed to help the student to recognize the national heroes of Indonesia which are integrated with technology so that they can use it anytime and anywhere